95. Pre and Post-Operative Radiation Protection in Ru-106 Opthalmic Brachytherapy. (December 2018) - Rossi, F.; Belli, G.; Fedeli, L.; Gori, C.; Genovese, E.; Cannatà, V.; Busoni, S.
Abstract : Purpose: The use of 106 Ru plaque was introduced for choroidal melanomas therapy. The aim of this study is workers and public exposure evaluation, in pre and post-operative phase of the treated patient. In particular attenuation properties of selected shielding materials and exposure levels around patient head and transport/sterilisation safety containers are reported. Methods: Exposure was measured around the head of five patients, in multiple positions at various distances from the skin. Dose rates around the transport/sterilisation container were also measured. Attenuation measurements were performed simulating the eye with a 25mm diameter plastic sphere, filled with water and the plaque attached on it. All measurements were performed with a calibrated instrumentations. Selected materials attenuation properties were measured in "narrow" beam mode (IEC 61331-1:2014). A custom code was developed to perform numerical simulation of BS spectrum. Results: In Table HVLs and TVLs for selected materials and the average exposure levels (±SD) measured around patients are reported. Five positions around the head, at 10 cm distance from the skin were considered, plus two positions at 1m. Exposure levels around the transport container are nearly constant for any given direction; average values is 1.6 μSv/h/MBq at contact and 0.013 μSv/h/MBq at 1 m. Conclusions: Considering typical activity of the implanted plaques, and conservative recovery and assistance times, up to 60 patients may be treated in a year, without exceeding 1mSv/y for post-operative activities. For the same number of patients, even considering a 8 hours/day standing at 1.5 m from the patient bed, the worker received dose is around 0.65 mSv/y. Attenuation properties for selected materials were measured and agree with simulated results. Main contribution to exposure comes from X- γ radiation, BS is almost negligible from radiation protection point of view.